1989
DOI: 10.1159/000248355
|View full text |Cite
|
Sign up to set email alerts
|

Psoriasis and Lichen planus: Coexistence in a Single Patient

Abstract: The coexistence of psoriasis and lichen planus has been rarely reported, although both diseases are relatively common and have some features in common. A rare case of simultaneous occurrence of both diseases is presented. Spontaneous improvement of psoriasis occurred during the development of lichen planus and a subsequent disappearance of the lichen planus was associated with an exacerbation of the psoriasis. The clinical courses of the two diseases may not be independent of each other, but be affected by com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 9 publications
0
11
0
Order By: Relevance
“…Other bowel diseases occasionally described concomitant with LP include coeliac disease (Lundstrom et al, 1982;Fortune and Buchanan, 1993) and Crohn's disease (Kano et al, 1995), though others have not found these associations . (14) MISCELLANEOUS ASSOCIATIONS LP has occasionally been associated with other conditions, including psoriasis (Shiohara et al, 1989;Naldi et al, 1990;Delaney et al, 1993), lichen sclerosis , urolithiasis (Halevy and Feuerman, 1983), agents used to treat gallstones (Ellul et al, 1992), mesangioproliferative glomerulonephritis (Cottoni et al, 1988), erythema dyschromicum (Berger et al, 1989), and Turner's syndrome with endocrinopathies (Kurgansky and Burnett, 1994).…”
Section: (8) Stressmentioning
confidence: 99%
“…Other bowel diseases occasionally described concomitant with LP include coeliac disease (Lundstrom et al, 1982;Fortune and Buchanan, 1993) and Crohn's disease (Kano et al, 1995), though others have not found these associations . (14) MISCELLANEOUS ASSOCIATIONS LP has occasionally been associated with other conditions, including psoriasis (Shiohara et al, 1989;Naldi et al, 1990;Delaney et al, 1993), lichen sclerosis , urolithiasis (Halevy and Feuerman, 1983), agents used to treat gallstones (Ellul et al, 1992), mesangioproliferative glomerulonephritis (Cottoni et al, 1988), erythema dyschromicum (Berger et al, 1989), and Turner's syndrome with endocrinopathies (Kurgansky and Burnett, 1994).…”
Section: (8) Stressmentioning
confidence: 99%
“…Some authors speculated about an underlying imbalance of TNF‐α and IFN‐γ as a result of an antigenic stimulus that caused superimposed linear LP lesions in a psoriatic patient . Local production of IFN‐γ was assigned to an improvement of psoriasis during development of LP in another case report . Apart from well‐described T‐cellular inflammatory mechanisms in psoriasis, high activation of innate immune pathways may lead to enhanced epidermal antigen release which could pave the way to an anti‐epithelial reaction and development of other inflammatory skin diseases.…”
Section: Discussionmentioning
confidence: 99%
“…The coexistence of psoriasis and typical LP has been rarely reported (4, 5). It has been suggested that this coexistence LP is probably underreported in the literature (4). The reasons for such association remain obscure.…”
Section: Discussionmentioning
confidence: 99%
“…The coexistence of psoriasis with typical LP or bullous pemphigoid has been previously reported (4–7), but the reason for such association remains obscure. However, a central role for T‐cell mediated autoimmunity has been suggested for all three disorders.…”
Section: Introductionmentioning
confidence: 99%